Evaluación de la inyección cíclica de solvente (C3) en el campo Apiay para la formación T2 mediante simulación numérica (2021)
One of the greatest challenges of the Oil Industry in the country, is to ensure the production and maintenance of the productive life of the oil fields present in the Colombian territory, that is why the need arises to implement new techniques of improved recovery. Thus, in the present degree thesis, the evaluation of the cyclic injection of solvent C3 for the T2 Formation of the Apiay Field, located in the Basin of the Eastern Plains, a description of the geological conditions of the Formation and the construction of the static and dynamic models compared together with the normal five-point water injection pattern of the Formation under study. This project was evaluated with the design and numerical simulation of the scenarios proposed for the cyclic injection of the solvent for each well present in the array, in which parameters such as: injection cycles, soaking time were modified, injection days and production days; the injection rate was set from a sensitivity analysis for each of the wells; and where the recovery factor, from the best scenarios, is compared to the prediction of the base scenario (water injection) over a period of ten years, in order to define the best method of recovery for T2 Training technically and financially. Based on these findings, conclusions and recommendations are presented.